(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study looked at the connections between self-leadership behaviours and supervisor performance ratings, objective work performance, and job happiness in nine Chinese organisations to see if the notion of self-leadership could be used in a non-Western setting. We also looked at how job autonomy could affect how self-leadership behaviours and these work outcomes relate to one another. We examined 407 supervisor-subordinate pairs from a range of businesses in Hong Kong and the People’s Republic of China. The findings revealed a favourable correlation between subordinates’. Even after adjusting for the personality attribute of conscientiousness, self-leadership behaviours are still associated with supervisor performance ratings and work satisfaction. Self-leadership, however, was not substantially correlated with actual work success. The associations between selfleadership behaviours and work outcomes like as performance rating, objective work performance, and job satisfaction were also affected by job autonomy. These results showed that the relationships between self-leadership and professional success identified in Western-based studies may be extrapolated to the Chinese organisational contexts examined in this study.